An 8-year retrospective review of microbial keratitis in a secondary referral centre in Malaysia - Omar, Nazri; Abdul Muna'aim, Maimunah; Md. Saleh, Rafidah; Mohd Kasim, Zaidah; Mohd Isa, Muhammad (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Introduction: Microbial keratitis (MK) is an important cause for corneal blindness and understanding its risk factors enable us to improve management and minimise its complications. Methods: In this retrospective case review, medical records of all patients treated for MK from 2006 to 2013 was analysed to know the socio-demography, preceding risk factors, clinical characteristics, causative organisms and final visual outcome. Results: A total of 174 patients (180 eyes) were included in this study. Identifiable ocular risk factors included contact lens (CL) usage (85, 47.2%), ocular trauma (50, 27.8%), ocular surface disease (21, 11.6%), steroid use (6, 3.3%) and immuno-compromy (19, 10.5%). Association factors for presenting uncorrected visual acuity (UCVA) were age group (p=0.013), size (p<0.001), location (p<0.001) and hypopyon (p<0.001). The predictors for final best spectacle-corrected visual acuity (BSCVA) were age group (p<0.001), nationality (p=0.020), occupation (p<0.001), CL use (p<0.001), ocular surface disease (p=0.048), size (p<0.001) and location (p<0.044), hospitalisation duration (p=0.002) and presenting UCVA (p<0.001). Conclusions: Contact lens was the most frequent predisposing risk factor for microbial keratitis, followed by ocular trauma. Understanding the association factors for presenting vision and predictors for final vision may help in the patients’ management and improve eventual outcome of microbial keratitis.